2019
DOI: 10.1007/s10660-019-09362-7
|View full text |Cite
|
Sign up to set email alerts
|

Cash flow prediction: MLP and LSTM compared to ARIMA and Prophet

Abstract: Cash flow prediction is important. It can help increase returns and improve the allocation of capital in healthy, mature firms as well as prevent fast-growing firms, or firms in distress, from running out of cash. In this paper, we predict accounts receivable cash flows employing methods applicable to companies with many customers and many transactions such as e-commerce companies, retailers, airlines and public transportation firms with sales in multiple regions and countries. We first discuss "classic" forec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(36 citation statements)
references
References 12 publications
(14 reference statements)
2
25
0
Order By: Relevance
“…Thus, this serves to motivate the study of machinelearning techniques within financial forecasting. As an illustration, [15] reviewed corporate cash flow forecasting using account receivable data collected through a specialized accounting software, which provides a richer view of the individual transactions.…”
Section: Conventional Approaches To Financial Forecastingmentioning
confidence: 99%
“…Thus, this serves to motivate the study of machinelearning techniques within financial forecasting. As an illustration, [15] reviewed corporate cash flow forecasting using account receivable data collected through a specialized accounting software, which provides a richer view of the individual transactions.…”
Section: Conventional Approaches To Financial Forecastingmentioning
confidence: 99%
“…As a result of the review of the scientific literature, regarding the implementation of techniques based on Machine Learning, for the approach of predictive solutions supported in time series, it was identified that the “Multi-Layered Perceptron” technique of the category Artificial Neural Networks has produced very good results in different fields of action, such as: investment models based on mutual funds [ 34 , 35 ], epidemiological models [ 35 , 36 ], estimation of the water recharge rate underground [ 37 , 38 ], analysis of the pedals interactions of race car drivers [ 39 ], efficient energy systems based on the prediction of natural gas consumption [ 40 , 41 ], and money flow prediction [ 42 ], among other studies.…”
Section: Contributionsmentioning
confidence: 99%
“…Network traffic forecasting is made based on network elements and affected by various factors such as the location of network elements, weather, and traffic on different base stations. Forecasting is mainly implemented via Gompertz models or time series forecasting models like LSTM and Prophet models [8,9,10]. The traffic forecast made based on traditional Extended Gompertz Models (EGMs) cannot reflect traffic differences between working days and holidays.…”
Section: Lstm Model For Traffic Forecastingmentioning
confidence: 99%